2023
DOI: 10.1371/journal.pgph.0002145
|View full text |Cite
|
Sign up to set email alerts
|

Applying community health systems lenses to identify determinants of access to surgery among mobile & migrant populations with hydrocele in Zambia: A mixed methods assessment

Abstract: Hydrocele which is caused by long term lymphatic filariasis infection can be treated through the provision of surgery. Access to surgeries remains low particularly for hard to reach populations. This study applied community health system lenses to identify determinants to the adoption, implementation and integration of hydrocele surgeries among migrants &mobile populations in Luangwa District, Zambia. A concurrent mixed methods design consisting of cross-sectional survey with hydrocele patients (n = 438) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In this study, examples of adaptations included delivery of integrated and adolescent-friendly HIV, GBV, and SRH services. Further, relational strategies could enhance implementation processes by providing an opportunity to accommodate diverse actors, interests, and expressions of power that characterize the CHS (19,20,25,31). Relational approaches can support adoption and sustainability of strategies by promoting shared communication and understanding of implementation problems and increased cohesion (38, 41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, examples of adaptations included delivery of integrated and adolescent-friendly HIV, GBV, and SRH services. Further, relational strategies could enhance implementation processes by providing an opportunity to accommodate diverse actors, interests, and expressions of power that characterize the CHS (19,20,25,31). Relational approaches can support adoption and sustainability of strategies by promoting shared communication and understanding of implementation problems and increased cohesion (38, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that use of community-based actors and structures in delivering and disseminating services can enhance adoption and acceptability of services by promoting their relevance and legitimacy (42)(43)(44). Further, community-engaged dissemination and implementation processes can also improve penetration and sustainability by facilitating or enabling co-production and co-learning among various implementing partners (19,20,25,31). This study demonstrated co-production through instances such as community involvement in developing by-laws and support groups for people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation